Revealing the intratumoral heterogeneity of non-DS acute megakaryoblastic leukemia in single-cell resolution - Su, Narun; Li, Zifeng; Yang, Jiapeng; Fu, Yang; Zhu, Xiaohua; Miao, Hui; Yu, Yi; Jiang, Wenjin; Le, Jun; Qian, Xiaowen; Wang, Hongsheng; Qian, Maoxiang; et al. (Frontiers in Oncology, 2022)
Pediatric acute megakaryoblastic leukemia (AMKL) is a subtype of acute myeloid leukemia (AML) characterized by abnormal megakaryoblasts, and it is divided into the AMKL patients with Down syndrome (DS-AMKL) and AMKL patients without DS (non–DS-AMKL). Pediatric non-DS-AMKL is a heterogenous disease with extremely poor outcome. We performed single-cell RNA sequencing (scRNA-seq) of bone marrow from two CBFA2T3-GLIS2 fusion positive and one RBM15-MKL1 fusion positive non-DS-AMKL children. Meanwhile we download the scRNA-seq data of normal megakaryocyte (MK) cells of fetal liver and bone marrow from healthy donors as normal controls. We conducted cell clustering, cell type identification, inferCNV analysis, GO, KEGG enrichment, monocle2 analysis to investigate the intratumoral heterogeneity of AMKL. Using canonical markers, we identified and characterized the abnormal blasts and other normal immune cells from three AMKL samples. We found the intratumoral heterogeneity of AMKL in the various cell type proportions, malignant cells’ diverse copy number variations (CNVs), maturities, significant genes expressions and enriched pathways. We also identified potential markers for pediatric AMKL, namely RACK1, ELOB, TRIR, NOP53, SELENOH, CD81. Our works offer insight into the heterogeneity of pediatric acute megakaryoblastic leukemia, and established the single-cell transcriptomic landscape of AMKL for the first time.